Low-friction wear-resistant antibacterial composite coating based on micro-arc oxidation as well as preparation method and application of low-friction wear-resistant antibacterial composite coating

By using microarc oxidation technology to form an oxide film on the surface of the titanium alloy and adding gallium oxide to the electrolyte, a low-friction wear-resistant and antibacterial composite coating was prepared, which solved the problems of insufficient mechanics, tribology, antibacterial and corrosion resistance of titanium alloys in clinical applications, and achieved better biomedical performance.

CN119710863AActive Publication Date: 2025-03-28JILIN JIANZHU UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411741064.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-28
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

Titanium alloys have insufficient mechanical properties, tribological properties, antibacterial properties and corrosion resistance in the clinical treatment of orthodontics, resulting in surface friction damage, bacterial infection and corrosion.

Method used

Microarc oxidation technology is used to form a dense oxide film on the surface of the titanium alloy, and gallium oxide is added as an antibacterial agent to the electrolyte to optimize the process parameters to prepare a low-molescent wear-resistant and antibacterial composite coating.

Benefits of technology

It improves the mechanical, tribological and corrosion resistance of the surface of titanium alloy, while also imparts antibacterial properties to effectively prevent bacterial infection and corrosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710863A_ABST
    Figure CN119710863A_ABST
Patent Text Reader

Abstract

The invention discloses a low-friction wear-resistant antibacterial composite coating based on micro-arc oxidation and a preparation method and application of the low-friction wear-resistant antibacterial composite coating based on micro-arc oxidation. The preparation method comprises the following steps that 1, a titanium alloy is subjected to oil removal, grinding, polishing and cleaning pretreatment; 2, the pretreated titanium alloy is immersed in a prepared electrolyte, micro-arc oxidation treatment is conducted, a micro-arc oxidation coating is obtained, and the electrolyte comprises sodium metasilicate, sodium hydroxide and gallium oxide; and step 3, cleaning and drying the micro-arc oxidation coating to obtain the low-friction wear-resistant antibacterial composite coating. The composite coating has good antibacterial property, mechanical property, tribological property and corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of surface treatment, and in particular to a low-friction, wear-resistant and antibacterial composite coating based on micro-arc oxidation, and a preparation method and application thereof. Background Art

[0002] Metal materials are widely used in the biomedical field, including dental materials, orthopedic materials, soft tissue repair materials and auxiliary treatment materials. At present, the metal materials commonly used in clinical orthodontic treatment include titanium alloy, nickel-titanium alloy and austenitic stainless steel. The materials used in orthodontic treatment must meet the requirements of being biomaterials, that is, in addition to having good biocompatibility, they also need to have excellent mechanical properties, tribological properties, antibacterial properties and corrosion resistance. Titanium and titanium alloys have gradually become one of the preferred materials in clinical orthodontic treatment due to their good biocompatibility. However, the mechanical and tribological properties of titanium alloys themselves are poor. When used clinically, friction damage easily occurs on their surfaces, resulting in the generation of wear debris, which triggers a series of inflammatory reactions and causes great pain to patients. In addition, titanium alloys do not have antibacterial ability and are prone to bacterial infection when used clinically. Infection is a common problem faced by biomaterials in clinical use and the biggest problem that plagues clinicians. This is related to improper operation during treatment and changes in the local environment of biomaterials, which affects the growth of microorganisms and increases the possibility of bacterial infection. Titanium alloys are used in the oral cavity for a long time as medical materials. At the same time, they must also meet the requirements of long-term use in the oral environment without corrosion leading to material failure. Therefore, it is particularly important to improve the mechanical, tribological, antibacterial and corrosion resistance of titanium alloys. Micro-arc oxidation technology is one of the effective methods to solve the above problems. Through this technology, a micro-arc oxidation coating mainly composed of oxides can be grown in situ on the surface of titanium alloys. As a typical hard ceramic coating, this coating is dense and has high bonding strength with titanium alloys, which can effectively improve the mechanical and tribological properties of the titanium alloy surface. In corrosive media, the micro-arc oxidation coating can also protect the titanium alloy from corrosion. Considering the application of titanium alloys in the biomedical field, how to further realize the multifunctional integration of micro-arc oxidation coatings on the surface of titanium alloys with mechanical, tribological, antibacterial and corrosion resistance has become a new problem. The composition of the electrolyte in micro-arc oxidation technology is an important parameter affecting the performance of the coating. By introducing antibacterial additives into the electrolyte and optimizing the process parameters, the low friction, wear resistance, antibacterial and corrosion resistance of the micro-arc oxidation coating can be achieved without weakening the original performance of the micro-arc oxidation coating, which is expected to solve the above problems.

[0003] Research has found that gallium oxide can effectively hinder the formation of bacterial biofilms, inhibit bacterial growth and has bactericidal activity. The antibacterial mechanism of gallium oxide is different from that of antibiotics. Its antibacterial mechanism relies on chemical mimicry, which is directly related to its "iron-like properties". 3+ with Fe3+ The chemical properties of Ga 3+ Can replace Fe 3+ Participate in physiological metabolism, Ga 3+ In replacing the Fe as the redox active center of the protein 3+ After that, it can inhibit the physiological activity of related proteins, thus acting as Fe 3+ competitive inhibitor to exert its function. 3+ It plays an important role in the formation of biofilm. 3+ As a coenzyme, Ga participates in many redox-related enzymes in cells. 3+ In replacing Fe 3+ After that, it cannot play the same role, so the formation of biofilm is blocked, and the bacterial infection ability is also inhibited. Gallium oxide is an inorganic antibacterial agent. Foreign literature reports that gallium oxide has good antibacterial properties against Acinetobacter baumannii and others. There are few related domestic literatures, mainly focusing on the effects on the formation of biofilms of Staphylococcus epidermidis and Escherichia coli. In addition, in two different animal infection models of acute pneumonia and respiratory biofilm infection, gallium oxide also showed quite good effects. At present, the research on gallium oxide is mainly focused on its preparation and optical properties, and there are relatively few studies on its antibacterial properties. Gallium oxide is a solid powder that can be evenly dispersed in the electrolyte. It can give the coating antibacterial properties through micro-arc oxidation technology, and has broad application prospects.

[0004] Therefore, the present invention mainly adopts micro-arc oxidation technology to treat titanium alloy. The obtained micro-arc oxidation coating effectively improves the mechanical, tribological and corrosion resistance of titanium alloy. On this basis, gallium oxide is added to the electrolyte as an antibacterial agent to obtain a low-friction, wear-resistant and antibacterial composite coating. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a low-friction, wear-resistant and antibacterial composite coating based on micro-arc oxidation in view of the technical defects in the prior art.

[0006] Another object of the present invention is to provide application of the composite coating on the surface of titanium alloy.

[0007] The technical solution adopted to achieve the purpose of the present invention is:

[0008] A method for preparing a low-friction, wear-resistant and antibacterial composite coating based on micro-arc oxidation comprises the following steps:

[0009] Step 1, pre-treating the titanium alloy by degreasing, grinding, polishing and cleaning;

[0010] Step 2, immersing the pretreated titanium alloy into a prepared electrolyte for micro-arc oxidation treatment to obtain a micro-arc oxidation coating, wherein the electrolyte comprises sodium metasilicate, sodium hydroxide, and gallium oxide;

[0011] Step 3, cleaning and drying the micro-arc oxidation coating to obtain a low-friction, wear-resistant and antibacterial composite coating.

[0012] In the above technical solution, in step 1, the degreasing specifically includes: cleaning the titanium alloy after wire cutting with an alkaline solution; immersing the titanium alloy in a 5-10% sodium hydroxide solution for 15-20 minutes, taking it out, and rinsing it with deionized water to remove the sodium hydroxide solution remaining on the surface.

[0013] In the above technical solution, in the step 1, the polishing specifically includes: polishing the titanium alloy after surface degreasing using 200#, 400#, 600#, 800#, 1000#, 1500#, and 2000# sandpaper in sequence.

[0014] In the above technical solution, in step 1, after polishing, the surface finish Ra of the titanium alloy is less than 0.8.

[0015] In the above technical scheme, in the step 1, the cleaning specifically includes: the polished titanium alloy is first placed in acetone for ultrasonic cleaning for 25 to 30 minutes, then placed in anhydrous ethanol for ultrasonic cleaning for 25 to 30 minutes, and finally ultrasonically cleaned in deionized water for 3 to 5 minutes, and dried at 60°C to obtain the pretreated titanium alloy.

[0016] In the above technical solution, in step 2, the concentration of sodium metasilicate in the electrolyte is 10-20 g / L, the concentration of sodium hydroxide is 1.5-2 g / L, and the concentration of gallium oxide is 2-20 g / L. Preferably, the concentration of gallium oxide is 10-20 g / L.

[0017] In the above technical scheme, in step 2, during the micro-arc oxidation treatment, the pretreated titanium alloy is used as the anode, a hole is punched in the pretreated titanium alloy, an aluminum wire is passed through the hole to immerse the pretreated titanium alloy in the prepared electrolyte, a stainless steel plate is used as the cathode, a pulse voltage is used as the voltage of the micro-arc oxidation, and the electrolyte is stirred by a stirrer during the micro-arc oxidation process, and the temperature of the electrolyte is controlled by a circulating water system; preferably, the electrolyte temperature is below 25°C, the forward voltage is 300-400V, the negative voltage is 50-70V, and the current density is 4-6A / dm 2 , the duty cycle is 10-20%, the frequency is 300-500Hz, the oxidation time is 3-5min, and the distance between the anode and cathode is 50-60mm.

[0018] Another aspect of the present invention also includes a low-friction, wear-resistant and antibacterial composite coating prepared by the method.

[0019] Another aspect of the present invention also includes the use of the low-friction, wear-resistant and antibacterial composite coating in biomedical materials.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] 1. The present invention prepares a low-friction, wear-resistant and antibacterial composite coating on the surface of a medical titanium alloy through micro-arc oxidation technology, thereby improving the mechanical and tribological properties of the titanium alloy surface, and the presence of a surface oxide film improves its corrosion resistance. Gallium oxide antibacterial agent is added to the electrolyte to form a micro-arc oxidation coating containing antibacterial elements, which not only gives the micro-arc oxidation coating antibacterial properties, but also gallium oxide and the micro-arc oxidation coating synergistically improve the mechanical properties, tribological properties and corrosion resistance of the entire coating.

[0022] 2. The choice of substrate determines the composition of the micro-arc oxidation coating. In the present invention, titanium alloy is used as the substrate, and gallium oxide is compounded into the micro-arc oxidation coating through micro-arc oxidation technology. The obtained coating effectively overcomes the shortcomings of titanium alloy as a biomedical material, that is, high friction coefficient and poor wear resistance.

[0023] 3. The raw materials used in the present invention are green, environmentally friendly, non-toxic and pollution-free; the preparation process is simple and easy to operate; the production efficiency is high and suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is a schematic diagram of a micro-arc oxidation device;

[0025] Figure 2 This is the surface morphology of the common micro-arc oxidation coating of Comparative Example 1;

[0026] Figure 3 This is the surface morphology of the low-friction, wear-resistant and antibacterial composite coating of Example 4;

[0027] Figure 4 This is the cross-sectional morphology of the common micro-arc oxidation coating of Comparative Example 1;

[0028] Figure 5 This is the cross-sectional morphology of the low-friction, wear-resistant and antibacterial composite coating of Example 4;

[0029] Figure 6 The mechanical properties of low-friction, wear-resistant and antibacterial composite coatings with different gallium oxide contents;

[0030] Figure 7 is the friction coefficient of low-friction, wear-resistant and antibacterial composite coatings with different gallium oxide contents;

[0031] Figure 8The self-corrosion current and potential of untreated titanium alloy and low-friction wear-resistant and antibacterial composite coatings with different gallium oxide contents;

[0032] Fig. 9 This is a scanning electron micrograph of the adhesion of untreated titanium alloy to Streptococcus mutans;

[0033] Fig.10 is a scanning electron microscope of the adhesion of the common micro-arc oxidation coating of Comparative Example 1 to Streptococcus mutans;

[0034] Fig.11 This is a scanning electron microscope image of the adhesion of the low-friction, wear-resistant, antibacterial composite coating of Example 4 to Streptococcus mutans.

[0035] In the figure: 1-cooling tank, 3-electrolyte, 4-stirring system, 5-coolant return pipe, 6-coolant inlet pipe DETAILED DESCRIPTION

[0036] The present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0037] Example 1

[0038] A method for preparing a low-friction, wear-resistant and antibacterial composite coating on the surface of a medical titanium alloy using micro-arc oxidation technology comprises the following steps:

[0039] Step 1: pre-treat the titanium alloy: including degreasing, grinding, polishing, and cleaning; the specific steps are as follows:

[0040] Degreasing: Immerse the titanium alloy in 5-10% sodium hydroxide solution for 15-20 minutes, then take it out and rinse it with deionized water to remove the residual sodium hydroxide solution on the surface;

[0041] Grinding: Grind the titanium alloy after degreasing the surface, and use 200#, 400#, 600#, 800#, 1000#, 1500#, and 2000# sandpaper in turn;

[0042] Polishing: The titanium alloy after surface grinding is polished to make its surface finish reach Ra less than 0.8;

[0043] Cleaning: The polished titanium alloy is first placed in a beaker filled with acetone, and then ultrasonically cleaned for 30 minutes at a temperature of 60-70°C and a frequency of 35-45KHz. It is then placed in a beaker filled with anhydrous ethanol and ultrasonically cleaned for 30 minutes at a temperature of 60-70°C and a frequency of 35-45KHz. Finally, it is ultrasonically cleaned with deionized water for 5 minutes at a temperature of 60-70°C and a frequency of 75-85KHz, and then placed in a 60°C oven for drying to obtain the pretreated titanium alloy.

[0044] Step 2, immersing the pretreated titanium alloy into the prepared electrolyte, performing micro-arc oxidation treatment, and obtaining a micro-arc oxidation coating; the specific steps are as follows:

[0045] like Figure 1 As shown, the pretreated titanium alloy obtained in step 1 is immersed in an electrolyte 3 containing 20 g / L sodium metasilicate, 2 g / L sodium hydroxide, and 2 g / L gallium oxide through an aluminum wire, the electrolyte 3 is located in a cooling tank 1, and the electrolyte is mixed evenly through a stirring system 4, a cold water interlayer is provided on the cooling tank 1, and the temperature of the electrolyte is controlled by a circulating water system, the cold water interlayer is provided with a coolant return pipe 5 and a coolant inlet pipe 6, and then the pretreated titanium alloy (micro-arc oxidation sample 2) and the stainless steel electrolytic cell are respectively connected to the anode and cathode of a micro-arc oxidation pulse DC power supply through a wire to obtain a connected micro-arc oxidation device, and the following embodiments and comparative examples all use the micro-arc oxidation device;

[0046] Turn on the connected pulse DC power supply of the micro-arc oxidation device. In the constant voltage mode, the positive pulse voltage is 300V, the negative pulse voltage is 50V, the positive pulse duty cycle is 10%, the negative pulse duty cycle is 10%, and the current density is 6A / dm 2 The micro-arc oxidation treatment was carried out for 5 minutes at an operating parameter of a frequency of 500 Hz to obtain a micro-arc oxidation coating.

[0047] Step 3, post-treating the micro-arc oxidation coating to obtain a low-friction, wear-resistant and antibacterial composite coating.

[0048] The micro-arc oxidation coating obtained in step 2 is ultrasonically cleaned with deionized water to remove residual electrolyte on the surface, and then blow-dried with a hair dryer to obtain a low-friction, wear-resistant and antibacterial composite coating.

[0049] Example 2

[0050] A method for preparing a low-friction, wear-resistant and antibacterial composite coating on the surface of a medical titanium alloy using micro-arc oxidation technology comprises the following steps:

[0051] Step 1: pre-treat the titanium alloy: including degreasing, grinding, polishing, and cleaning; the specific steps are as follows:

[0052] Degreasing: Immerse the titanium alloy in 5-10% sodium hydroxide solution for 15-20 minutes, then take it out and rinse it with deionized water to remove the residual sodium hydroxide solution on the surface;

[0053] Grinding: Grind the titanium alloy after degreasing the surface, and use 200#, 400#, 600#, 800#, 1000#, 1500#, and 2000# sandpaper in turn;

[0054] Polishing: The titanium alloy after surface grinding is polished to make its surface finish reach Ra less than 0.8;

[0055] Cleaning: The polished titanium alloy is first placed in a beaker filled with acetone, and then ultrasonically cleaned for 30 minutes at a temperature of 60-70°C and a frequency of 35-45KHz. It is then placed in a beaker filled with anhydrous ethanol and ultrasonically cleaned for 30 minutes at a temperature of 60-70°C and a frequency of 35-45KHz. Finally, it is ultrasonically cleaned with deionized water for 5 minutes at a temperature of 60-70°C and a frequency of 75-85KHz, and then placed in a 60°C oven for drying to obtain the pretreated titanium alloy.

[0056] Step 2, immersing the pretreated titanium alloy into the prepared electrolyte, performing micro-arc oxidation treatment, and obtaining a micro-arc oxidation coating. The specific steps are as follows:

[0057] The pretreated titanium alloy obtained in step 1 is immersed in an electrolyte containing 20 g / L sodium metasilicate, 2 g / L sodium hydroxide, and 4 g / L gallium oxide through an aluminum wire, and the electrolyte is mixed evenly through a stirring system 4, and then the pretreated titanium alloy and the stainless steel electrolytic cell are respectively connected to the anode and cathode of the micro-arc oxidation pulsed DC power supply through a wire to obtain a connected micro-arc oxidation device;

[0058] Turn on the connected pulse DC power supply of the micro-arc oxidation device. In the constant voltage mode, the positive pulse voltage is 300V, the negative pulse voltage is 50V, the positive pulse duty cycle is 10%, the negative pulse duty cycle is 10%, and the current density is 6A / dm 2 The micro-arc oxidation treatment was carried out for 5 minutes at an operating parameter of a frequency of 500 Hz to obtain a micro-arc oxidation coating.

[0059] Step 3, post-treating the micro-arc oxidation coating to obtain a low-friction, wear-resistant and antibacterial composite coating.

[0060] The micro-arc oxidation coating obtained in step 2 is ultrasonically cleaned with deionized water to remove residual electrolyte on the surface, and then blow-dried with a hair dryer to obtain a low-friction, wear-resistant and antibacterial composite coating.

[0061] Example 3

[0062] A method for preparing a low-friction, wear-resistant and antibacterial composite coating on the surface of a medical titanium alloy using micro-arc oxidation technology comprises the following steps:

[0063] Step 1: pre-treat the titanium alloy: including degreasing, grinding, polishing, and cleaning; the specific steps are as follows:

[0064] Degreasing: Immerse the titanium alloy in 5-10% sodium hydroxide solution for 15-20 minutes, then take it out and rinse it with deionized water to remove the residual sodium hydroxide solution on the surface;

[0065] Grinding: Grind the titanium alloy after degreasing the surface, and use 200#, 400#, 600#, 800#, 1000#, 1500#, and 2000# sandpaper in turn;

[0066] Polishing: The titanium alloy after surface grinding is polished to make its surface finish reach Ra less than 0.8;

[0067] Cleaning: The polished titanium alloy is first placed in a beaker filled with acetone, and then ultrasonically cleaned for 30 minutes at a temperature of 60-70°C and a frequency of 35-45KHz. It is then placed in a beaker filled with anhydrous ethanol and ultrasonically cleaned for 30 minutes at a temperature of 60-70°C and a frequency of 35-45KHz. Finally, it is ultrasonically cleaned with deionized water for 5 minutes at a temperature of 60-70°C and a frequency of 75-85KHz, and then placed in a 60°C oven for drying to obtain the pretreated titanium alloy.

[0068] Step 2, immersing the pretreated titanium alloy into the prepared electrolyte, performing micro-arc oxidation treatment, and obtaining a micro-arc oxidation coating. The specific steps are as follows:

[0069] The pretreated titanium alloy obtained in step 1 is immersed in an electrolyte containing 20 g / L sodium metasilicate, 2 g / L sodium hydroxide, and 10 g / L gallium oxide through an aluminum wire, and the electrolyte is mixed evenly through a stirring system 4, and then the pretreated titanium alloy and the stainless steel electrolytic cell are respectively connected to the anode and cathode of the micro-arc oxidation pulsed DC power supply through a wire to obtain a connected micro-arc oxidation device;

[0070] Turn on the connected pulse DC power supply of the micro-arc oxidation device. In the constant voltage mode, the positive pulse voltage is 300V, the negative pulse voltage is 50V, the positive pulse duty cycle is 10%, the negative pulse duty cycle is 10%, and the current density is 6A / dm 2 The micro-arc oxidation treatment was carried out for 5 minutes at an operating parameter of a frequency of 500 Hz to obtain a micro-arc oxidation coating.

[0071] Step 3, post-treating the micro-arc oxidation coating to obtain a low-friction, wear-resistant and antibacterial composite coating.

[0072] The micro-arc oxidation coating obtained in step 2 is ultrasonically cleaned with deionized water to remove residual electrolyte on the surface, and then blow-dried with a hair dryer to obtain a low-friction, wear-resistant and antibacterial composite coating.

[0073] Example 4

[0074] A method for preparing a low-friction, wear-resistant and antibacterial composite coating on the surface of a medical titanium alloy using micro-arc oxidation technology comprises the following steps:

[0075] Step 1: pre-treat the titanium alloy: including degreasing, grinding, polishing, and cleaning; the specific steps are as follows:

[0076] Degreasing: Immerse the titanium alloy in 5-10% sodium hydroxide solution for 15-20 minutes, then take it out and rinse it with deionized water to remove the residual sodium hydroxide solution on the surface;

[0077] Grinding: Grind the titanium alloy after degreasing the surface, and use 200#, 400#, 600#, 800#, 1000#, 1500#, and 2000# sandpaper in turn;

[0078] Polishing: The titanium alloy after surface grinding is polished to make its surface finish reach Ra less than 0.8;

[0079] Cleaning: The polished titanium alloy is first placed in a beaker filled with acetone, and then ultrasonically cleaned for 30 minutes at a temperature of 60-70°C and a frequency of 35-45KHz. It is then placed in a beaker filled with anhydrous ethanol and ultrasonically cleaned for 30 minutes at a temperature of 60-70°C and a frequency of 35-45KHz. Finally, it is ultrasonically cleaned with deionized water for 5 minutes at a temperature of 60-70°C and a frequency of 75-85KHz, and then placed in a 60°C oven for drying to obtain the pretreated titanium alloy.

[0080] Step 2, immersing the pretreated titanium alloy into the prepared electrolyte, performing micro-arc oxidation treatment, and obtaining a micro-arc oxidation coating, specifically comprising the following steps:

[0081] The pretreated titanium alloy obtained in step 1 is immersed in an electrolyte containing 20 g / L sodium metasilicate, 2 g / L sodium hydroxide, and 20 g / L gallium oxide through an aluminum wire, and the electrolyte is mixed evenly through a stirring system 4. Then, the pretreated titanium alloy and the stainless steel electrolytic cell are connected to the anode and cathode of the micro-arc oxidation pulsed DC power supply through wires, respectively, to obtain a schematic diagram of a connected micro-arc oxidation device as shown in FIG. Figure 1 As shown;

[0082] Turn on the connected pulse DC power supply of the micro-arc oxidation device. In the constant voltage mode, the positive pulse voltage is 300V, the negative pulse voltage is 50V, the positive pulse duty cycle is 10%, the negative pulse duty cycle is 10%, and the current density is 6A / dm 2 The micro-arc oxidation treatment was carried out for 5 minutes at an operating parameter of a frequency of 500 Hz to obtain a micro-arc oxidation coating.

[0083] Step 3, post-treating the micro-arc oxidation coating to obtain a low-friction, wear-resistant and antibacterial composite coating.

[0084] The micro-arc oxidation coating obtained in step 2 is ultrasonically cleaned with deionized water to remove residual electrolyte on the surface, and then blow-dried with a hair dryer to obtain a low-friction, wear-resistant and antibacterial composite coating.

[0085] Comparative Example 1

[0086] A method for preparing a common micro-arc oxidation coating on the surface of a medical titanium alloy using micro-arc oxidation technology comprises the following steps:

[0087] Step 1: pre-treat the titanium alloy: including degreasing, grinding, polishing, and cleaning; the specific steps are as follows:

[0088] Degreasing: Immerse the titanium alloy in 5-10% sodium hydroxide solution for 15-20 minutes, then take it out and rinse it with deionized water to remove the residual sodium hydroxide solution on the surface;

[0089] Grinding: Grind the titanium alloy after degreasing the surface, and use 200#, 400#, 600#, 800#, 1000#, 1500#, and 2000# sandpaper in turn;

[0090] Polishing: The titanium alloy after surface grinding is polished to make its surface finish reach Ra less than 0.8;

[0091] Cleaning: The polished titanium alloy is first placed in a beaker filled with acetone, and then ultrasonically cleaned for 30 minutes at a temperature of 60-70°C and a frequency of 35-45KHz. It is then placed in a beaker filled with anhydrous ethanol and ultrasonically cleaned for 30 minutes at a temperature of 60-70°C and a frequency of 35-45KHz. Finally, it is ultrasonically cleaned with deionized water for 5 minutes at a temperature of 60-70°C and a frequency of 75-85KHz, and then placed in a 60°C oven for drying to obtain the pretreated titanium alloy.

[0092] Step 2, immersing the pretreated titanium alloy into the prepared electrolyte, performing micro-arc oxidation treatment, and obtaining a micro-arc oxidation coating; the specific steps are as follows:

[0093] The pretreated titanium alloy is immersed in an electrolyte containing 20 g / L sodium metasilicate and 2 g / L sodium hydroxide through an aluminum wire, and the electrolyte is mixed evenly through a stirring system 4, and then the pretreated titanium alloy and the stainless steel electrolytic cell are respectively connected to the anode and cathode of the micro-arc oxidation pulse DC power supply through the wire to obtain a connected micro-arc oxidation device;

[0094] Turn on the connected pulse DC power supply of the micro-arc oxidation device. In the constant voltage mode, the positive pulse voltage is 300V, the negative pulse voltage is 50V, the positive pulse duty cycle is 10%, the negative pulse duty cycle is 10%, and the current density is 6A / dm 2The micro-arc oxidation treatment was carried out for 5 minutes at an operating parameter of a frequency of 500 Hz to obtain a micro-arc oxidation coating.

[0095] Step 3, post-treating the micro-arc oxidation coating to obtain a composite coating.

[0096] The micro-arc oxidation coating obtained in step 2 is ultrasonically cleaned with deionized water to remove residual electrolyte on the surface, and then blow-dried with a hair dryer to obtain a common micro-arc oxidation coating.

[0097] Analysis of the results of Examples 1-4 and Comparative Example 1:

[0098] The surfaces of the ordinary micro-arc oxidation coating obtained in Comparative Example 1 and the low-friction, wear-resistant and antibacterial composite coating obtained in Example 4 are as follows: Figure 2-Figure 3 As shown, the cross-sectional scanning electron microscopy of the ordinary micro-arc oxidation coating obtained in Comparative Example 1 and the low-friction wear-resistant antibacterial composite coating obtained in Example 4 is as follows: Figure 4-Figure 5 By comparing the surface morphology of the ordinary micro-arc oxidation coating and the low-friction, wear-resistant and antibacterial composite coating, it can be found that the porosity and pore size of the low-friction, wear-resistant and antibacterial composite coating are reduced. At the same time, in the cross-sectional view, it is found that the dense layer of the low-friction, wear-resistant and antibacterial composite coating is thicker and more uniform, and its loose layer has fewer pores than the ordinary micro-arc oxidation coating. The thickness of the low-friction, wear-resistant and antibacterial composite coating is about 4μm. The above results show that the low-friction, wear-resistant and antibacterial composite coating has a better mechanical structure.

[0099] The coatings obtained in Comparative Example 1 and Examples 1 to 4 were tested for mechanical properties using a nanoindenter. The test results are as follows: Figure 6 As shown, it can be seen that compared with Comparative Example 1, the hardness and elastic modulus of the low-friction, wear-resistant and antibacterial composite coatings obtained in Examples 1 to 4 are improved, especially the low-friction, wear-resistant and antibacterial composite coating obtained under the highest gallium oxide concentration conditions in Example 4 has a hardness of 13.5 GPa and an elastic modulus of 113 GPa, showing the best mechanical properties.

[0100] Then, the coatings obtained in Comparative Example 1 and Examples 1 to 4 were subjected to a ball-disc friction tester (TRB 3 CSM, Anton Paar) along a circular track with a diameter of 1 mm, and the friction pair was a stainless steel ball (6 mm, Shanghai Panlian Technology). The results are shown in Figure 7 As shown in , the friction coefficient of comparative example 1 is 0.22. Although the friction coefficient shows an increasing trend with the increase of gallium oxide concentration, we soon discovered that with the further increase of gallium oxide concentration, the friction coefficient gradually decreases, reaching a minimum of 0.14 in Example 4, showing a more excellent low friction performance.

[0101] In addition, from the scanning electron microscope comparison image, we also found that the porosity and pore size of the low-friction, wear-resistant and antibacterial composite coating were reduced. At the same time, the cross-sectional image showed that the dense layer of the low-friction, wear-resistant and antibacterial composite coating was thicker and more uniform, and its loose layer had less pore structure than the ordinary micro-arc oxidation coating, and the overall film thickness was about 4μm.

[0102] The samples obtained in Comparative Example 1 and Examples 1 to 4 were placed in an artificial saliva environment using an electrochemical workstation to test their corrosion resistance. Figure 8 As shown in the figure, the self-corrosion current of the low-friction, wear-resistant and antibacterial composite coatings with different concentrations of gallium oxide, namely, Examples 1 to 4, decreases with the increase of potential, indicating that passivation occurs. The dense oxide film on the surface of the coating hinders ion diffusion, and the self-corrosion potential E corr Both are an order of magnitude higher than pure titanium and have better corrosion resistance.

[0103] Mutans Streptococcus (type S. mutans, ATCC25175) was used to test the bacterial adhesion of untreated titanium alloy, ordinary micro-arc oxidation coating and low-friction wear-resistant antibacterial composite coating. The results are as follows: Figure 9-11 As shown, it can be seen that the low-friction, wear-resistant and antibacterial composite coating exhibits the best anti-bacterial adhesion, while there are more bacteria adhering to the surface of the ordinary micro-arc oxidation coating, and the mutans streptococci on the untreated titanium alloy surface even show clustered accumulation, indicating that the presence of gallium oxide makes the low-friction, wear-resistant and antibacterial composite coating have excellent anti-bacterial adhesion.

[0104] In summary, when the concentration of gallium oxide in the electrolyte is 10-20 g / L, the comprehensive performance is better than that of 2-4 g / L. When the concentration of gallium oxide in the electrolyte is higher than 20 g / L, the biocompatibility will be relatively lost. Therefore, the best performance corresponds to a gallium oxide concentration of 10-20 g / L.

[0105] The above is only a preferred embodiment of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a low-friction, wear-resistant and antibacterial composite coating based on micro-arc oxidation, characterized in that: The following steps are involved: Step 1, pre-treating the titanium alloy by degreasing, grinding, polishing and cleaning; Step 2, immersing the pretreated titanium alloy into a prepared electrolyte for micro-arc oxidation treatment to obtain a micro-arc oxidation coating, wherein the electrolyte includes sodium metasilicate, sodium hydroxide, and gallium oxide; Step 3, cleaning and drying the micro-arc oxidation coating to obtain a low-friction, wear-resistant and antibacterial composite coating.

2. The preparation method according to claim 1, characterized in that In the step 1, the degreasing specifically includes: cleaning the titanium alloy after wire cutting with an alkali solution; immersing the titanium alloy in a 5-10% sodium hydroxide solution for 15-20 minutes, then taking it out and rinsing it with deionized water to remove the sodium hydroxide solution remaining on the surface.

3. The preparation method according to claim 1, characterized in that: In the step 1, the polishing specifically includes: polishing the titanium alloy after surface degreasing using 200#, 400#, 600#, 800#, 1000#, 1500#, and 2000# sandpaper in sequence.

4. The preparation method according to claim 1, characterized in that: In the step 1, after polishing, the surface finish Ra of the titanium alloy is less than 0.

8.

5. The preparation method according to claim 1, characterized in that: In step 1, the cleaning specifically includes: the polished titanium alloy is first placed in acetone for ultrasonic cleaning for 25 to 30 minutes, then placed in anhydrous ethanol for ultrasonic cleaning for 25 to 30 minutes, and finally ultrasonically cleaned in deionized water for 3 to 5 minutes, and dried at 60°C to obtain the pretreated titanium alloy.

6. The preparation method according to claim 1, characterized in that: In step 2, the concentration of sodium metasilicate in the electrolyte is 10-20 g / L, the concentration of sodium hydroxide is 1.5-2 g / L, and the concentration of gallium oxide is 2-20 g / L. Preferably, the concentration of gallium oxide is 10-20 g / L.

7. The preparation method according to claim 1, characterized in that: In the step 2, during the micro-arc oxidation treatment, the pretreated titanium alloy is used as the anode, a hole is punched in the pretreated titanium alloy, an aluminum wire is passed through the hole to immerse the pretreated titanium alloy in the prepared electrolyte, a stainless steel plate is used as the cathode, and a pulse voltage is used as the voltage of the micro-arc oxidation. During the micro-arc oxidation process, the electrolyte is stirred by a stirrer, and the temperature of the electrolyte is controlled by a circulating water system.

8. The preparation method according to claim 7, characterized in that: In step 2, during the micro-arc oxidation treatment, the electrolyte temperature is below 25°C, the forward voltage is 300-400V, the negative voltage is 50-70V, and the current density is 4-6A / dm 2 , the duty cycle is 10-20%, the frequency is 300-500Hz, the oxidation time is 3-5min, and the distance between the anode and cathode is 50-60mm.

9. A low-friction, wear-resistant and antibacterial composite coating prepared by the method according to any one of claims 1 to 8.

10. Use of the low-friction, wear-resistant and antibacterial composite coating according to claim 9 in biomedical materials.

Citation Information

Patent Citations

  • Method for regulating and controlling diversification of color layer of color pupil through electric field

    CN117572667A

  • Corrosion and erosion-resistant mixed oxide coatings for the protection of chemical and plasma process chamber components

    US20140318974A1